Teaching EFL Reading Skills with Instructional Scaffolding Microlectures: Chinese Non-English Major Undergraduates’ Performances and Perceptions - Liu, Lisha (Advances in Social Sciences Research Journal, 2018)
Teacher - centred lecturing, the dominated teaching style at Chinese universities is facing enormous challenges as microlectures prevail in higher education pedagogy nowadays. Some Chinese lecturers have begun exploring how to use microlectures in their own programmes in order to improve their teaching performances and students’ learning outcome. However, currently, the teaching practice of using microlectures in college English classes seems to be still at a trial stage, which creates much space for our further investigation into its teaching effects. This paper describes a study conducted at Southern University of Science and Technology, which seeks to explore non-English major undergraduates’ performances through and perceptions of teaching English reading skills with instructional scaffolding microlectures. After an analysis of 34 1st-year undergraduates’ standardized reading tests, self-evaluation sheets of reading skills and reading course feedback self-reports, the findings show that this teaching method can improve students’ English language proficiency, learning interest and independence effectively.